Aktivitas Enzim Antioksidan Pada Akar Eleocharis dulcis (Burm.F.) Trin. Ex Henschel Dalam Fitoremediasi Air Asam Tambang Batubara Di Wetland Air Laya 02 - Wike Agung Safitri; Juswardi Juswardi (Mahesa Research Center, 2023)
Acid mine drainage (AMD) formed from open pit mining can cause environmental impacts if discharged directly into the waters because it has a low pH and contains heavy metals. Attempts to neutralize the pH and absorb heavy metals in AMD can be carried out by means of phytoremediation using Eleocharis dulcis (Burm.f.) Trin. Ex Henschel. This study aims to determine the activity of PO, PPO, and CAT on the roots of E. dulcis in AMD phytoremediation and evaluate the success of AMD phytoremediation. Sampling using convenience sampling method. Measurement of metal content of Fe and Mn with atomic absorption spectrophotometer (AAS). Protein extraction using refrigerated centrifugation, measurement of total protein content with BSA, and activity of PO, PPO and CAT using a uv-vis spectrophotometer. Based on research that has been done, E. dulcis is able to increase the pH from 5.6 to 7.7 and reduce Fe levels from 7.88 mg/l to 0.25 mg/l, Mn 1.71 mg/l to 0.75 mg /l. The physiological response shown by E. dulcis in AMD phytoremediation was an increase in antioxidant enzyme activity PO 178.98 U/mg protein/minute, PPO 388.96 U/mg protein/minute and CAT 184.34 U/mg protein/minute. Based on research, E. dulcis is a plant that is tolerant to pH stress and heavy metals, so it has the potential to be used in AMD phytoremediation.